Modern and fossil pollen record from region of the middle Araguaia River floodplain, Tocantins State (Brazil) - MENDES, Lais Aguiar da Silveira; MENESES, Maria Ecilene Nunes da Silva; BEHLING, Hermann; COSTA, Marcondes Lima da (Pesquisas em Geociências, 2021)
Abstract. The Araguaia river is one of the most important hydrographic basin in Brazil. Its drainage system reaches two dominant Brazilian biomes that are Amazon Rainforest and Brazilian Cerrado (savanna). This study was carried out in a zone of ecotone between rainforest and savanna formations, in the Middle Araguaia River basin, specifically at the floodplain of Javaés River its tributary by right margin, in the State of Tocantins. The goal of this present study was to provide information about the vegetational succession in this forest-savanna ecotone area, in order to contribute to the understanding of this landscape dynamics. For this reason, a sedimentary core collected from a lake (Lago da Mata Verde) was submitted to palynological and radiocarbon dating analyses. The results showed that during the last 400 years this site was bordered by forest reflecting a wet climate with some increase of the flooded margins in the present day. The modern pollen rain and local vegetation data supported in the interpretation of the fossil pollen results. Our findings are according to other studies carried out in the similar ecotone zones and floodplains in Amazonian regions during the Late Holocene. Keywords. Lacustrine sediments, Late Holocene, pollen analysis. Resumo. O rio Araguaia constitui uma das mais importantes bacias hidrográficas brasileiras. Seu sistema de drenagem atravessa dois dominantes biomas brasileiros a saber o bioma Amazônico e o Cerrado brasileiro (savanas). Este estudo, foi realizado em uma zona de ecótono entre as formações de floresta tropical e savana, na bacia do Médio Rio Araguaia, especificamente na planície de inundação do rio Javaés, seu tributário pela margem direita, no estado do Tocantins. O objetivo deste estudo foi fornecer informações sobre a sucessão vegetal nesta área de ecótono floresta-savana, visando contribuir para o entendimento da dinâmica desta paisagem. Dessa forma, um testemunho sedimentar coletado no Lago da Mata Verde foi submetido às análises palinológicas e de datação radiocarbônica. Os resultados mostraram que durante os últimos 400 anos este ambiente foi cercado por floresta refletindo um clima úmido, com um ligeiro aumento de margens inundadas nos dias atuais. Os dados de chuva polínica atual e de vegetação local fundamentaram a interpretação dos resultados palinológicos fósseis. Os resultados obtidos são similares a outros estudos realizados em outras áreas de ecótonos e planícies de inundação em regiões da Amazônia durante o Holoceno Tardio. Palavras-chave. Sedimentos lacustres, Holoceno Tardio, análises palinológicas